Associated factors of overweight in adolescents from public schools in Northern Minas Gerais State, Brazil - Lucinéia de Pinho; Ana Cristina de C. Botelho; Antônio Prates Caldeira (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: In order to support plans and actions that combat the local increasing overweight and obesity prevalence in adolescents, the factors associated to weight excess in public school students from Montes Claros, MG, Southeast Brazil, were studied.METHODS: Cross-sectional study with a sample of adolescents from the public schools of the city. The nutritional status was evaluated and an inquiry was carried out in the schools to determine food consumption and practice of physical activities. Factors associated to weight excess were assessed by bivariate analysis followed by logistic regression.RESULTS: Weight excess prevalence was detected in 18.5% of the 535 adolescents evaluated. The factors associated to weight excess were: per capita income above half minimum wage (OR 1.99; 95%CI 1.01-3.93), candy consumption above two daily portions (OR 1.94; 95%CI 1.13-3.32) and absence of sport activity during leisure time (OR 2.54; 95%CI 1.15-5.59).CONCLUSIONS: The proportion of weight excess in adolescents from public schools is relevant and associated with socioeconomic condition of the family, bad eating habits and sedentary life.